Generation of iPSC line iPSC-FH2.1 in hypoxic conditions from human foreskin fibroblasts - Questa, María (2016)
Human foreskin fibroblasts were used to generate the iPSC line iPSC-FH2.1 using the EF1a-hSTEMCCA-loxP vector expressing OCT4, SOX2, c-MYC and KLF4, in 5% O2 culture conditions. Stemness was confirmed, as was pluripotency both in vivo and in vitro, in normoxia and hypoxia. Human Embryonic Stem Cell (hESC) line WA-09 and reprogrammed fibroblast primary culture HFF-FM were used as controls.